2016
DOI: 10.18632/oncotarget.10971
|View full text |Cite
|
Sign up to set email alerts
|

CD24 promoted cancer cell angiogenesis via Hsp90-mediated STAT3/VEGF signaling pathway in colorectal cancer

Abstract: CD24 is involved in tumor progression of various cancers, but the effects of CD24 on tumor angiogenesis in colorectal cancer are still unknown. We aimed to investigate the underlying mechanism and role of CD24 on colorectal cancer (CRC) angiogenesis. Our data showed that the microvessal density (MVD) was related to the expression of CD24 in primary and metastasis CRC. Silencing of CD24 could dramatically decrease human umbilical vein endothelial cell (HUVEC) migration, invasion and tubule formation, but trivia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…25 The authors suggested that Src was the kinase linking CD24 to the activation of STAT3. 48 We show that early activation of STAT3 is required to obtain an increased expression of SOX2. 47 In contrast, in our experiments, we did not observe any effect of the Src kinase inhibitors PP2 or dasatinib on the vem-mediated phosphorylation of STAT3.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…25 The authors suggested that Src was the kinase linking CD24 to the activation of STAT3. 48 We show that early activation of STAT3 is required to obtain an increased expression of SOX2. 47 In contrast, in our experiments, we did not observe any effect of the Src kinase inhibitors PP2 or dasatinib on the vem-mediated phosphorylation of STAT3.…”
Section: Discussionmentioning
confidence: 76%
“…A recent study on colorectal cancer has shown that Hsp90 can serve as a signaltransmitting link between CD24 and STAT3. 48 We show that early activation of STAT3 is required to obtain an increased expression of SOX2. This initial STAT3 activation might be due to secreted factors as suggested by Ohanna et al showing that the secretome of senescent melanoma cells drives basal melanoma cells toward a mesenchymal phenotype and activates the STAT3 pathway.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, hypoxia in solid tumors induced CD24 expression via Hypoxia Inducible Factor-1 leading to increased tumor cell survival (Thomas et al, 2012). Finally, CD24 has been shown to regulate angiogenesis through Heat Shock Protein 90 and modulation of the STAT3/VEGF pathway (Wang et al, 2016). Therefore, CD24 is also important for modulating the sensitivity or cellular response to extracellular stresses.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that HSP90 regulates angiogenesis at least partially by modulating stability of CD24 in colorectal cancer cells. [8,9] Consistently, it has been shown that HSP90 inhibitors elicit anti-angiogenic properties in tumour cells. [10] In line with this, Lang et al showed that inhibition of HSP90 by 17-dimethylaminoethylamino-17-demethoxygeldanamycin (17-DMAG) exerts anti-angiogenic effect by inhibiting the growth and vascularization of gastric tumours in tumour models.…”
Section: Angiogenesismentioning
confidence: 82%